Effect of metformin on adverse outcomes in T2DM patients: Systemic review and meta-analysis of observational studies - Xu, Zhicheng; Zhang, Haidong; Wu, Chenghui; Zheng, Yuxiang; Jiang, Jingzhou (Frontiers in Cardiovascular Medicine, 2022)
Background The cardiovascular protection effect of metformin on patients with type 2 diabetes mellitus (T2DM) remains inconclusive. This systemic review and meta-analysis were to estimate the effect of metformin on mortality and cardiovascular events among patients with T2DM. Methods A search of the Pubmed and EMBASE databases up to December 2021 was performed. Adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) were pooled by a random-effects model with an inverse variance method. Results A total of 39 studies involving 2473009 T2DM patients were adopted. Compared to non-metformin therapy, the use of metformin was not significantly associated with a reduced risk of major adverse cardiovascular event (MACE) (HR = 1.06, 95%CI 0.91–1.22; I2 = 82%), hospitalization (HR = 0.85, 95%CI 0.64–1.13; I2 = 98%), heart failure (HR = 0.86, 95%CI 0.60–1.25; I2 = 99%), stroke (HR = 1.16, 95%CI 0.88–1.53; I2 = 84%), and risk of AMI (HR = 0.88, 95%CI 0.69–1.14; I2 = 88%) in T2DM patients. Metformin was also not associated with significantly lowered risk of MACE compared to dipeptidyl peptidase-4 inhibitor (DPP-4i) in T2DM patients (HR = 0.95, 95%CI 0.73–1.23; I2 = 84%). Conclusions The effect of metformin on some cardiovascular outcomes was not significantly better than the non-metformin therapy or DPP-4i in T2DM patients based on observational studies.